2017
DOI: 10.1111/jnc.13993
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors and hormones pro‐peptides: the unexpected adventures of the BDNF prodomain

Abstract: Most growth factors and hormones are synthesized as prepro-proteins which are processed to the biologically active mature protein. The pre-and prodomains are cleaved from the precursor protein in the secretory pathway or, in some cases, extracellularly. The canonical functions of these prodomains are to assist in folding and stabilization of the mature domain, to direct intra and extracellular localization, to facilitate storage, and to regulate bioavailability of their mature counterpart. Recently, exciting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 88 publications
0
29
0
Order By: Relevance
“…This has been the case with most fungal effector 412 Pro-domains are found in a diverse range of proteins, and are best known for their roles in 444 controlling activity in proteases and hormones. They have also been implicated in stabilisation and 445 correct folding of these proteins (Baker et al, 1993;Zanin et al, 2017). We found that inclusion 446 of the pro-domain is crucial for producing soluble cysteine-rich effector proteins in E. coli.…”
Section: Discussion 386mentioning
confidence: 68%
“…This has been the case with most fungal effector 412 Pro-domains are found in a diverse range of proteins, and are best known for their roles in 444 controlling activity in proteases and hormones. They have also been implicated in stabilisation and 445 correct folding of these proteins (Baker et al, 1993;Zanin et al, 2017). We found that inclusion 446 of the pro-domain is crucial for producing soluble cysteine-rich effector proteins in E. coli.…”
Section: Discussion 386mentioning
confidence: 68%
“…BDNF protein also exists in 2 different forms, the unprocessed proBDNF and the smaller, processed mature BDNF (matBDNF). These 2 forms of protein have different receptors and cellular effects, so it is again important to assess both forms of BDNF . Both proBDNF and matBDNF were upregulated by cocaine CPP training within the NAc (Figure G,I; t (6) = 3.8, P = .009; t (6) = 2.8, P = .03).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of central or peripheral neurons with sub-nanomolar concentrations of proNGF or proBDNF induces the rapid collapse of growth cones via actin depolymerization (Deinhardt et al, 2011). Increasing evidence also shows that the pro-domain of BDNF has a bioactivity on its own (Je et al, 2012;Mizui et al, 2017;Zanin et al, 2017) whereas so far little was attempted to characterize the properties of the NGF pro-domain and how they relate to the properties of the same region within the context of proNGF (Clewes et al, 2008).…”
Section: Discussionmentioning
confidence: 99%